Farmers’ perception of plant protection in Ranga Reddy district of Telangana, India - Kumari, B Ratna; Rao, G V Ranga; Sahrawat, K L; Rajasekhar, P; Rao, V Rameshwar; Wani, S P (Indian Journal of Plant Protection, 2020)
A survey to learn farmers’ perception of plant protection in Kothapally (contact village) and Enkepally (noncontact) villages of Ranga Reddy district of Telangana, India indicated that 80-86% of the farmers undertake plant protection practices based on the first appearance of the pest. Thirty eight per cent of the farmers in Kothapally, and 50% in Enkepally got their plant protection advice from pesticide dealers and 35% in Kothapally and 20% of the farmers in Enkepally implemented plant protection according to the advice from the agricultural officers. Though 100% of the farmers used chemical pesticides for pest control, a majority (88%) of them felt that the chemicals used were not effective which could be due to spuriousness and occurrence of insecticide resistance in key species. Only 32% of the farmers in Kothapally and 12% in Enkepally were aware and adopted protective clothing. Amongst the various health problems, farmers complained of headache as the major. Forty four per cent of the farmers in Kothapally were aware of the residual effects of pesticides compared to only 16% in the noncontact village. The details of chemical use in different crops in the two villages were also discussed.